Trigonelline nanocrystal-based topical creams for the treatment of hair loss - K. Shreya Shetty; Marina Koland; Ashwini, M. Marina (Journal of Advanced Pharmaceutical Technology & Research)
This study aimed to develop a topical nanoparticulate form of trigonelline to enhance delivery to hair follicles and promote hair growth, addressing the limitations of conventional topicals. Trigonelline nanocrystals were synthesized using sonoprecipitation and optimized through the Box–Behnken design. The optimized nanocrystals were analyzed using scanning and transmission electron microscopy. In vitro permeation and in-vivo skin irritation tests were conducted. The effect on hair length and density was evaluated in cyclophosphamide-induced alopecia in Wistar rats. The optimized nanocrystals had a particle size of 142.7 nm, a polydispersity index of 0.137, and a zeta potential of −25.9 mV. The topical cream contained 79.0% drug. In vitro studies showed higher flux with high Trigonelline loading. In vivo tests indicated the product was innocuous. Hair length and density were significantly greater (P < 0.01) in the nanocrystal-treated group compared to controls and commercial hair oil, but not greater than the Minoxidil group after 30 days. Nanocrystal-based trigonelline formulations show promise for treating alopecia, potentially offering an alternative to minoxidil and finasteride.